2014
DOI: 10.1242/dev.107078
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear to cytoplasmic shuttling of ERK promotes differentiation of muscle stem/progenitor cells

Abstract: The transition between the proliferation and differentiation of progenitor cells is a key step in organogenesis, and alterations in this process can lead to developmental disorders. The extracellular signal-regulated kinase 1/2 (ERK) signaling pathway is one of the most intensively studied signaling mechanisms that regulates both proliferation and differentiation. How a single molecule (e.g. ERK) can regulate two opposing cellular outcomes is still a mystery. Using both chick and mouse models, we shed light on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 48 publications
6
81
1
1
Order By: Relevance
“…Future work will therefore focus on the possible interactions between DUSP5 and chemical inhibitors of ERK pathway components to better inform personalized therapy. Although it is logical to test compounds already in clinical use, it will be important to also examine emerging ERK-targeted compounds that are reported to act by inhibiting ERK dimerization (47) or nuclear translocation (48), as well as explore the possibility that DUSP5-specific inhibitors may be developed. It is likely that the most effective extension of our current work will be to determine the effects of Dusp5 loss in human cancer cell lines with different oncogenic backgrounds combined with the use of murine models that allow tissue-specific conditional expression of BRAF V600E and Dusp5 deletion to further define the in vivo significance of our results.…”
Section: Discussionmentioning
confidence: 99%
“…Future work will therefore focus on the possible interactions between DUSP5 and chemical inhibitors of ERK pathway components to better inform personalized therapy. Although it is logical to test compounds already in clinical use, it will be important to also examine emerging ERK-targeted compounds that are reported to act by inhibiting ERK dimerization (47) or nuclear translocation (48), as well as explore the possibility that DUSP5-specific inhibitors may be developed. It is likely that the most effective extension of our current work will be to determine the effects of Dusp5 loss in human cancer cell lines with different oncogenic backgrounds combined with the use of murine models that allow tissue-specific conditional expression of BRAF V600E and Dusp5 deletion to further define the in vivo significance of our results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as mentioned above, for all MAPKs, the sub-cellular localization of ERK1/2 is important for their regulation and physiological functioning [4, 23, 24, 39]. Accordingly, it was shown that the nuclear accumulation of ERK1/2 upon stimulation is important primarily for the induction of proliferation, while other ERK1/2-dependent processes are mostly regulated by cytoplasmic ERK1/2 [40, 41]. It should be noted, however, that in some tissues or cells, nuclear ERK1/2 was reported to induce differentiation, including neurite outgrowth of PC12 cells [42], or development of eyes and wings in Drosophila [43, 44].…”
Section: The Mechanism Of Mapks Translocation Into the Nucleusmentioning
confidence: 99%
“…51 These signaling pathways are presumed to facilitate the stability of Snail. ERK cascades are key signaling pathways involved in the regulation of multiple cellular processes, such as proliferation, 52 differentiation, 53 survival 54 and transformation. 55 The aberrant regulation of ERK signaling contributes to cancer and other human diseases.…”
Section: Mcp-1-induced Emt Of Mcf-7 Cells S LI Et Almentioning
confidence: 99%